Is ACWR related to injury risk in junior tennis players? - Vescovi, J. D. (Medicine & Science in Sports & Exercise, 2021)
Author's position concerning the study by Myers et al. (1) investigating the relationship between workload and injury risk in junior tennis players. Er bezieht sich auf weitere Quellen zum Thema (2, 3). 1. Myers NL, Aguilar KV, Mexicano G, Farnsworth JL 2nd, Knudson D, Kibler WB. The acute:chronic workload ratio is associated with injury in junior tennis players. Med Sci Sports Exerc. 2020;52(5):1196-200. 2. Orchard JW, James T, Portus M, Kountouris A, Dennis R. Fast bowlers in cricket demonstrate up to 3- to 4-week delay between high workloads and increased risk of injury. Am J Sports Med. 2009;37(6): 1186-92. 3. Vescovi JD. Acute:chronic training loads in tennis: which metrics should we monitor? Br J Sports Med. 2017;51(18):1321-2.